2012
DOI: 10.1590/s0104-11692012000100012
|View full text |Cite
|
Sign up to set email alerts
|

Functional disability of adult individuals with spinal cord injury and its association with socio-demographic characteristics

Abstract: The aim was to investigate the Functional Disability degree in adults with spinal cord injury and its association with socio-demographic characteristics. The Barthel Index was used and 75 subjects answered a questionnaire with socio-demographic variables. The Chi-Square, Cronbach's Alpha and Fisher tests were used in the analysis. The mean age was 42.23 years. Cronbach's Alpha for the Barthel Index was 0.807. The activities that were more difficult to perform were y Deambular (82,7%). La mediana del Índice de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
3
17
0
3
Order By: Relevance
“…These results, as well as those reported by other studies, confirm that urban violence and auto and occupational accidents are important causes of disabilities in Brazil, especially in large and medium urban centers (8)(9)(10)(11)(12) .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results, as well as those reported by other studies, confirm that urban violence and auto and occupational accidents are important causes of disabilities in Brazil, especially in large and medium urban centers (8)(9)(10)(11)(12) .…”
Section: Discussionsupporting
confidence: 89%
“…The socio-demographic profile of the study's participants corroborates that reported in the literature, which indicates that the population most affected by SCIs is young adult males aged between 18 and 35 years of age (8)(9)(10)(11) .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Some studies [2][3][4][5] identify cases of elderly people above 60 years with LM. However, specific nursing care with a focus on the elderly patient with this diagnosis are not well understood in the literature.…”
mentioning
confidence: 99%
“…Soon, people with 60 years of age with mild or severe disabilities live, although the injury has occurred in young age. 4 Why the need of the individual with LM have to readjust to perform basic activities of daily living (ABVD). 3,6 To assist individuals in the process of adjustment, systematization of nursing care…”
mentioning
confidence: 99%